Dimethyl sulfide facilitates acid catalysed ring opening of the bicyclic monoterpenes in crude sulfate turpentine to afford p-menthadienes in good yield. Issue 1 (24th December 2020) - Tibbetts, Joshua D.; Bull, Steven D.
Abstract : Dimethyl sulfide enables efficient acid-catalysed ring opening of bicyclic monoterpenes in turpentine to give p -menthadienes in up to 90% yields. Abstract : The potential of using turpentine for the production of biorenewable chemicals within a biorefinery context is discussed, focussing on the development of practical methodology to convert the bicyclic monoterpene components present in untreated crude sulfate turpentine into mixtures of synthetically useful p -menthadienes ( p -MeDs) as feedstocks for chemical production. A simple and scalable biphasic acid catalysed ring-opening (ACRO) protocol employing recyclable 6 M aq. H2 SO4 at 90 °C has been developed to transform the major bicyclic monoterpenes (β-pinene, α-pinene, and 3-carene) in untreated commercial crude sulfate turpentine (CST) into mixtures of monocyclic p -MeDs in >70% yield. Investigations using pure bicyclic monoterpenes reveal that the ∼3 mol% Me2 S present in CST plays a key role in increasing the rate and yield of these ACRO reactions. Reaction monitoring studies have identified the presence of induction periods and autocatalytic effects, as well as an intriguing time-dependent increase in p -MeD yield after all the bicyclic terpene substrate has been consumed. These effects have been explained using a mechanism that invokes reversible addition of Me2 S to the alkene bonds of monoterpenes to produce in situ generated sulfonium salts. These sulfonium salts then function as surfactants to increase the degree of mixing of the aqueous/terpene layers of the biphasic ACRO reaction, resulting in faster protonation of the alkene bonds of the bicyclic terpenes in the rate-determining step. The shorter reaction times of the Me2 S facilitated ACRO reactions of CST and gum turpentine enable better yields of p -MeDs to be obtained by minimising p -MeD losses to competing polymerisation pathways that occur at elevated temperatures over time.